Chronic Maternal Depressive Symptoms Are Associated With Reduced Socio-Emotional Development in Children at 2 Years of Age: Analysis of Data From an Intervention Cohort in Rural Pakistan - De Oliveira, Clariana V. R.; Rasheed, Muneera; Yousafzai, Aisha K. (Frontiers in Psychiatry, 2019)
Background: Maternal depression affects a high proportion of women during the antenatal and postnatal period in low- and middle-income countries. While maternal depression is recognized as a significant risk for poor early child development that warrants interventions, the effects of chronic maternal depression on children’s development is less understood. Objective: To determine the association of chronicity of maternal depressive symptoms and early child development in a rural population in southern Pakistan. Materials and Methods: This study employs data from the ‘Pakistan Early Child Development Scale-Up Trial,’ a randomized controlled study that evaluated the integration of responsive stimulation and nutrition interventions in a community health service. In the present analysis, linear regression was used to test the effects of chronicity of high maternal depressive symptoms on children’s early development (n=1205 mother-infant dyads). Children’s development was assessed using the Bayley Scales of Infant and Toddler Development at 24 months of age. Maternal depressive symptoms were assessed at baseline and every 6 months using the Self-Reporting Questionnaire. Results: No significant associations were observed between chronic maternal depressive symptoms and child cognitive, language or motor development after adjusting for parental characteristics, the caregiving environment and socioeconomic variables. A negative significant association between chronicity of high maternal depressive symptoms and child socio-emotional development (β coefficient -2.57, 95 % CI: -5.14;-0.04) was observed after adjusting for the selected variables. Conclusions: The results suggest that interventions designed to promote early child development should also integrate repeat screening for depression and longer-term psychosocial support for mothers.